Dominant negative mutations of caenorhabditis elegans daf‐7 confer a novel developmental phenotype. Issue 6 (28th April 2013) - Crook, Matt; Grant, Warwick N.
<x xml:space="preserve">Abstract</x> Background: TGF‐β signaling pathways are involved in the control of development in every member of the animal kingdom. As such, TGF‐β ligands are widely divergent yet retain a set of core conserved features, specifically, a pre‐protein cleavage site and several conserved ligand domain residues, the disruption of which produces a dominant negative phenotype. Results: We have extended these observations into an invertebrate system by creating a series of loss‐of‐function Caenorhabditis elegans daf‐7 transgenes. When we tested these mutant transgenes in a daf‐7/+ background, we saw a molting and excretory canal phenotype. Members of both pathways downstream of daf‐4 were required for this phenotype. Conclusions: Our results show that the basic mechanisms of TGF‐β function are conserved across the animal kingdom. A subset of our daf‐7 mutations also produced an unexpected and novel phenotype. Epistasis experiments demonstrated that both daf‐3/‐5 and sma‐4/‐9 were downstream of our mutant daf‐7 transgenes, which suggests not only a role for DAF‐7 in the control of molting and the development of the excretory system but also that daf‐7 and dbl‐1 signaling may converge downstream of their shared Type II receptor, daf‐4. Our approach may unveil new roles in development for other invertebrate TGF‐β ligands. Developmental Dynamics 242:654–664, 2013. © 2013 Wiley Periodicals, Inc.